(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2022)
The leaves of the binahong are part of the creeper that is easy to grow and develop. Binahong leaves are used for their bioactive content. Besides having many benefits, patchouli has a strong aroma and a distinctive smell. Binahong and patchouli leaves have not been widely used by the community, especially in making hand sanitizers. During the Covid 19 pandemic, hand sanitizers were sought after by many people. Hand sanitizer is a rare and valuable item in the community. This community service aims to provide knowledge on binahong and patchouli leaves in making hand sanitizers. Methods in community service in practice, surveys, and counseling. Binahong leaf extract is produced by immersing the binahong leaves in a 98% alcohol solution. Materials and manufacturing procedures follow WHO recommendations and literature review. This activity indicates the level of preference because the skin does not dry out quickly and has a distinctive aroma. The conclusion of this community service is that the use of binahong leaf extract and the addition of patchouli essential contributes to the knowledge of making hand sanitizers to the community. — Daun binahong merupakan bagian tanaman menjalar yang mudah tumbuh dan berkembang. Daun binahong dimanfaatkan karena kandungan bioaktifnya. Atsiri nilam selain memiliki banyak manfaat, memiliki aroma yang kuat dan bau yang khas. Daun binahong dan nilam belum banyak dimanfaatkan oleh masyarakat khususnya pembuatan hand sanitizer. Pada Masa pademi Covid 19, dimana hand sanitizer menjadi barang yang dicari banyak masyarakat. Handsanitizer menjadi barang langka dan berharga dimasyarakat. Pengabdian kepada masyarakat ini bertujuan untuk memberikan pengetahuan pemanfaatan daun binahong dan nilam pada pembuatan hand sanitizer. Metode pada pengabdian berupa survei, praktek dan pelatihan. Esktrak daun binahong dihasilkan dengan cara merendam daun binahong ke dalam larutan alkohol 98%. Bahan dan prosedur pembuatan mengikuti saran WHO dan literatur riview. Hasil kegiatan pengabdian ini menunjukkan tingkat kesukaan karena kulit tidak cepat kering dan memiliki aroma yang khas. Kesimpulan pada pengabdian masyarakat ini bahwa pemanfaatan ekstrak daun binahong dan penambahan atsiri nilam memberikan kontribusi pada pengetahuan pembuatan hand sanitizer kepada masyarakat.